Trunk Orientation, Stability, and Quadrupedalism - Ivanenko, Yuri P.; Wright, W. G.; St George, Rebecca; Gurfinkel, Victor S. (Frontiers in Neurology, 2013)
Interesting cases of human quadrupedalism described by Tan and Colleagues (2005–2012) have attracted the attention of geneticists, neurologists, and anthropologists. Since his first publications in 2005, the main attention has focused on the genetic aspects of disorders that lead to quadrupedalism within an evolutionary framework. In recent years this area has undergone a convincing critique (Downey, 2010) and ended with a call “… to move in a different direction … away from thinking solely in terms of genetic abnormality and evolutionary atavism.” We consider quadrupedalism as a “natural experiment” that may contribute to our knowledge of the physiological mechanisms underlying our balance system and our tendency toward normal (upright) posture. Bipedalism necessitates a number of characteristics that distinguish us from our ancestors and present-day mammals, including: size and shape of the bones of the foot, structure of the axial and proximal musculature, and the orientation of the human body and head. In this review we address the results of experimental studies on the mechanisms that stabilize the body in healthy people, as well as how these mechanisms may be disturbed in various forms of clinical pathology. These disturbances are related primarily to automatic rather than voluntary control of posture and suggest that human quadrupedalism is a behavior that can result from adaptive processes triggered by disorders in postural tone and environmental cues. These results will serve as a starting point for comparing and contrasting bi- and quadrupedalism.